Adenosine metabolism in the vascular system - Yegutkin Gennady G. (Pergamon Press, 2022)
The concept of extracellular purinergic signaling was first proposed by Geoffrey Burnstock in the early 1970s. Since then, extracellular ATP and its metabolites ADP and adenosine have attracted an enormous amount of attention in terms of their involvement in a wide range of immunomodulatory, thromboregulatory, angiogenic, vasoactive and other pathophysiological activities in different organs and tissues, including the vascular system. In addition to significant progress in understanding the properties of nucleotide- and adenosine-selective receptors, recent studies have begun to uncover the complexity of regulatory mechanisms governing the duration and magnitude of the purinergic signaling cascade. This knowledge has led to the development of new paradigms in understanding the entire purinome by taking into account the multitude of signaling and metabolic pathways involved in biological effects of ATP and adenosine and compartmentalization of the adenosine system. Along with the "canonical route" of ATP breakdown to adenosine via sequential ecto-nucleoside triphosphate diphosphohydrolase-1 (NTPDase1/CD39) and ecto-5'-nucleotidase/CD73 activities, it has now become clear that purine metabolism is the result of concerted effort between ATP release, its metabolism through redundant nucleotide-inactivating and counteracting ATP-regenerating ectoenzymatic pathways, as well as cellular nucleoside uptake and phosphorylation of adenosine to ATP through complex phosphotransfer reactions. In this review I provide an overview of key enzymes involved in adenosine metabolic network, with special emphasis on the emerging roles of purine-converting ectoenzymes as novel targets for cancer and vascular therapies.